THE EFFECT OF BLENDED LEARNING METHOD ASSISTED BY CHATBOT DARA APPLICATION ON FIFTH GRADE STUDENTS’ LEARNING OUTCOMES - Fitri, Hidayatul; Hermansyah; Setyaningrum, Vidya (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This research is motivated by the use of digital technology that has shown a positive impact on the academic presentation of students. Chatbot applications is one technology that can be utilized to improve the quality of learning in the classroom.The research method used is Quasi Experimental with pretest-postest control group design. The total population in this study were 128 5th grade students. The samples used were class 5B and Class 5C. Data collection techniques used tests and non-tests. The data collection instruments used were question sheets, observation sheets, and documentation guidelines. The analysis technique used was descriptive analysis and hypothesis testing.based on data analysis obtained: 1) Control class pretest learning outcomes was 34 while the posttest was 59. 2) Experimental class pretest learning outcomes was 46,77 while the posttest was 80,96. 3) There is a significant effect on the application of the blended learning method assisted by DARA chatbot application. with an effect size test of 9.1935. So it can be concluded that in general the use of blended learning methods assisted by DARA chatbot applications has a high influence on student learning outcomes.